POLA AKTIVITAS RUANG PUBLIK DI TAMAN SIRING TENDEAN BANJARMASIN - Syahriani Purnamasari (Universitas Lambung Mangkurat, 2019)
AbstractThe study is purposed to describe: (1) the pattern of activity in the Siring Tendean Park was dominantly carried out by the people who did economic activities. Because there are many street vendors (PKL) and floating market traders who were selling on weekends. Cultural activities, such as the cultural attractions and river trails, shown the characteristics of Banjar culture. Social activities are the community that conducts activities and visitors who interact, recreation and sports in Taman Siring Tendean, as well as students for educational activities. (2) The perceived benefits in terms of economy are the land for floating market traders, street vendors (PKL), and boat drivers (Kelotok) to develop their businesses. The social benefits are also felt by the community and visitors because they can communicate and avoid anti-social attitudes. Cultural benefits for actors of cultural attractions can provide a place for them to express themselves. Health benefits are able to blend in with nature and reduce stress level and also encouraging someone to do physical activities. The benefits of recreation are for refreshing and relaxing (3) The positive impact of the existence of Siring Tendean Park, namely that the economic impact can increase people income, social impacts can be used as a place for people interaction, self expression and recreation, the health effects is people can do some sport activitity and the cultural impact can preserve culture Banjar. While, the perceived negative impact is the amount of garbage, there is any conflict between traders and Satpol PP and conflicts between visitors.Keywords: activity, public space, siring tendean parkAbstrakTujuan penelitian mendeskripsikan; (1) pola aktivitas di Taman Siring Tendean dominan dilakukan oleh orang-orang yang melakukan kegiatan ekonomi. Karena ada banyak pedagang kaki lima (PKL) dan pedagang pasar terapung yang berjualan di akhir pekan. Kegiatan budaya, seperti atraksi budaya dan jalur sungai, menunjukkan karakteristik budaya Banjar. Kegiatan sosial adalah komunitas yang melakukan kegiatan dan pengunjung yang berinteraksi, rekreasi dan olahraga di Taman Siring Tendean, serta siswa untuk kegiatan pendidikan. (2) Manfaat yang dirasakan dalam hal ekonomi adalah tanah bagi pedagang pasar terapung, pedagang kaki lima (PKL), dan pengemudi perahu (Kelotok) untuk mengembangkan bisnis mereka. Manfaat sosial juga dirasakan oleh masyarakat dan pengunjung karena mereka dapat berkomunikasi dan menghindari sikap anti-sosial. Manfaat budaya bagi pelaku atraksi budaya dapat memberikan tempat bagi mereka untuk mengekspresikan diri. Manfaat kesehatan dapat menyatu dengan alam dan mengurangi tingkat stres dan juga mendorong seseorang untuk melakukan aktivitas fisik. Manfaat rekreasi adalah untuk menyegarkan dan bersantai (3) Dampak positif dari keberadaan Taman Siring Tendean, yaitu bahwa dampak ekonomi dapat meningkatkan pendapatan masyarakat, dampak sosial dapat digunakan sebagai tempat untuk interaksi orang, ekspresi diri dan rekreasi, dampak kesehatannya adalah orang dapat melakukan beberapa kegiatan olahraga dan dampak budaya dapat melestarikan budaya Banjar. Sementara, dampak negatif yang dirasakan adalah jumlah sampah, ada konflik antara pedagang dan Satpol PP dan konflik antara pengunjung.Kata Kunci: aktivitas, ruang publik, taman tendean siring